ENERGY DEFICIT AND MORTALITY IN CRITICALLY ILL COVID-19 PATIENTS: EXPLORING THE MODIFYING ROLE OF ARDS - I Putu Prayoga Ratha; Niken Puruhita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Critically ill patients with COVID‑19 frequently develop a hypermetabolic and catabolic state that increases energy and protein requirements, placing them at risk of cumulative nutritional deficits and poor clinical outcomes. This study aimed to evaluate the association between cumulative energy and protein deficits and intensive care unit (ICU) mortality and to explore whether acute respiratory distress syndrome (ARDS) modifies these relationships. A retrospective cohort study was conducted in 188 adult COVID‑19 patients who stayed in the ICU for at least seven days. Energy and protein requirements were determined according to ICU nutrition guidelines, while actual intake from enteral and parenteral nutrition was recorded over the first seven ICU days. Nutritional deficits were defined as intake <80% of the prescribed target and analyzed using multivariable logistic regression adjusted for age and comorbidities, with additional interaction terms for ARDS. Early energy deficit was independently associated with higher in‑hospital mortality, whereas protein deficit showed a similar direction of effect but did not reach statistical significance. Interactions between ARDS and either energy or protein deficits were not statistically significant, although effect estimates suggested a tendency toward greater harm in patients with severe respiratory failure and mechanical ventilation. These findings indicate that preventing early energy deficit is a key component of ICU nutrition therapy and may help improve outcomes in critically ill patients with COVID‑19. ABSTRAK Pasien COVID‑19 kritis sering mengalami kondisi hipermetabolik dan katabolik yang meningkatkan kebutuhan energi dan protein, sehingga berisiko mengalami defisit nutrisi yang dapat memperburuk luaran klinis. Penelitian ini bertujuan menilai hubungan defisit energi dan protein kumulatif dengan mortalitas di unit perawatan intensif (ICU) serta mengeksplorasi peran acute respiratory distress syndrome (ARDS) sebagai faktor pemoderasi. Studi kohort retrospektif ini melibatkan 188 pasien dewasa dengan COVID‑19 yang dirawat di ICU minimal tujuh hari. Kebutuhan energi dan protein ditentukan berdasarkan pedoman nutrisi ICU, sedangkan asupan aktual dihitung dari kombinasi catatan nutrisi enteral dan parenteral selama tujuh hari pertama perawatan. Defisit nutrisi didefinisikan sebagai asupan <80% dari target yang diresepkan, dan dianalisis menggunakan regresi logistik multivariat dengan penyesuaian terhadap usia serta komorbiditas, termasuk interaksi dengan ARDS. Defisit energi awal berhubungan secara independen dengan peningkatan risiko kematian di rumah sakit, sedangkan defisit protein menunjukkan arah efek yang konsisten namun tidak mencapai signifikansi statistik. Interaksi antara ARDS dan defisit energi atau protein tidak bermakna, tetapi estimasi efek menunjukkan kecenderungan dampak yang lebih besar pada pasien dengan gangguan respirasi berat dan kebutuhan ventilasi mekanik. Temuan ini menegaskan bahwa pencegahan defisit energi pada fase awal perawatan ICU merupakan komponen kunci tata laksana nutrisi yang berpotensi memperbaiki luaran pada pasien COVID‑19 kritis.